2015
DOI: 10.1103/physrevb.91.024504
|View full text |Cite
|
Sign up to set email alerts
|

Competing superconducting and magnetic order parameters and field-induced magnetism in electron-dopedBa(Fe1xCox)2As2

Abstract: We have studied the magnetic and superconducting properties of Ba(Fe 0.95 Co 0.05 ) 2 As 2 as a function of temperature and external magnetic field using neutron scattering and muon spin rotation. Below the superconducting transition temperature the magnetic and superconducting order parameters coexist and compete. A magnetic field can significantly enhance the magnetic scattering in the superconducting state, roughly doubling the Bragg intensity at 13.5 T. We perform a microscopic modelling of the data by use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
(195 reference statements)
1
10
0
Order By: Relevance
“…. Recent experimental studies have found evidence for the presence of magnetic fluctuations along with superconductivity below T c [51,52]. Studies in FeSe samples have shown evidence for BCS-BEC crossover in a Fermi system with strong spin imbalance, where the presence of preformed pairs in the crossover regime [33] was reported, namely, the possibility of superconducting fluctuations present above T c .…”
Section: Discussionmentioning
confidence: 99%
“…. Recent experimental studies have found evidence for the presence of magnetic fluctuations along with superconductivity below T c [51,52]. Studies in FeSe samples have shown evidence for BCS-BEC crossover in a Fermi system with strong spin imbalance, where the presence of preformed pairs in the crossover regime [33] was reported, namely, the possibility of superconducting fluctuations present above T c .…”
Section: Discussionmentioning
confidence: 99%
“…High resolution synchrotron x-ray data were collected at beamline 11BM-B of the Advanced Photon Source (APS) at Argonne National Laboratory (ANL) with λ = 0.414Å. Detailed structural analyses were performed using the Rietveld method as implemented in the FullProf, GSAS and EXPGUI software suites [21][22][23] . Inelastic neutron scattering (INS) experiments were carried out on HFIR's triple-axis spectrometer HB-3.…”
mentioning
confidence: 99%
“…The 233 family orders in non-centrosymmetric hexagonal P 6m2 space group symmetry with a structural motif of double-walled sub-nano tubes (DWS) coaxial to the caxis and of [(Cr 3 As 3 ) −2 ] ∞ stoichiometry (see Fig. 1(d)) while the A-site ion acting as a spacer/charge reservoir 'layer' 2,4,5 . DFT calculations predict a Fermi surface built of complex mixtures of the Cr 3d shells with strong Q1D character 3,6,7 .…”
mentioning
confidence: 99%
“…Condensation of singlet pairs enables us to probe the small spin response at q = 0. In Ba(Fe,Co) 2 As 2 , finite q spin fluctuations can freeze and exhibit long range antiferromagnetism in vortex cores [50]. In FeSe we see no evidence for such behavior, which may be due to the presence of nematic order and the different contribution of orbital versus spin susceptibility.…”
mentioning
confidence: 59%